Analysis of Factors Affecting Students' Learning Difficulties in Integration Science and Social Studies Subject in Madrasah Ibtidaiyah - Agung Haziz Indramanto; Sarah, Siti (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the factors contributing to students’ learning difficulties in the IPAS (Science and Social Studies) subject among fourth-grade students at Madrasah Ibtidaiyah in East Purwokerto District. This research employs a descriptive quantitative approach using a survey method. The instrument used was a questionnaire administered to a total population of 167 fourth-grade students from MIN 1 Banyumas and MI Diponegoro 1. Data were analyzed using Exploratory Factor Analysis (EFA). The results of the EFA test revealed seven main factors contributing to learning difficulties in the IPAS subject. The most dominant factor was students' learning interest at school, with the highest eigenvalue (3.870). The second factor was study habits at home (eigenvalue = 1.838), followed by community environment (1.714), student character (1.572), learning activities at school (1.296), family environment (1.045), and school environment (1.008).